A comparative study to assess the post-operative complications between laparoscopic cholecystectomy versus open cholecystectomy - Salwan, Anurag; Singh, Rana R.; Bansal, Darpan (International Surgery Journal, 2021)
Background: Cholelithiasis is a common problem these days. Earlier it was considered the health problem of the female only. But now it is quite common in the males also. The prevalence of gallbladder stone disease (GBSD) in female to male is 3:1 in 18-65 years age group. In the developed countries GBSD is common and occur in 7% in male and 15% in female with an overall prevalence of 11%. Cholecystectomy is one of the most common operation carried out in general surgery. Methods: Our study was conducted on 60 patients divided in 2 groups of 30 each to compare post-operative complications between laparoscopic cholecystectomy and open cholecystectomy. Results: As per findings of the present study duration of pain, rate of complications and total hospital stay were significantly lower in laparoscopic group. There was early removal of drainage tube, early stitch removal in laparoscopic group. Conclusions: Laparoscopic cholecystectomy can be recommended as first choice operative treatment for patients with cholelithiasis as it provides better cosmetic results, lesser pain, early removal of drainage tube, lesser post-operative hospital stay and fewer incidence of surgical site infection. It should be an available option for all patients requiring elective cholecystectomy.